2017
DOI: 10.1016/j.colsurfb.2017.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-multivalent binding of cholera toxin subunit B with glycolipid mixtures

Abstract: GM1 has generally been considered as the major receptor that binds to cholera toxin subunit B (CTB) due to its low dissociation constant. However, using a unique nanocube sensor technology, we have shown that CTB can also bind to other glycolipid receptors, fucosyl-GM1 and GD1b. Additionally, we have demonstrated that GM2 can contribute to CTB binding if present in a glycolipid mixture with a strongly binding receptor (GM1/fucosyl-GM1/GD1b). This hetero-multivalent binding result was unintuitive because the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 45 publications
3
54
1
Order By: Relevance
“…The available data, however, suggest that compared to the villi, the deeper parts of the intestinal membranes are unaffected by the non-functional FUT2 of non-secretors, due to expression of an alternative 1,2-fucosyltransferase encoded by the H gene 65, 67 . Non-secretors cannot secrete soluble ABO(H) glycans, but might still present suitable docking sites (i.e., Le y ) on these deeper membrane regions, independent of their secretor status, and cooperative binding is expected to be enhanced for hetero-multivalent binding including GM1 55 . Indeed, Cervin et al observed tighter binding of CTB to the crypts than to the villi 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available data, however, suggest that compared to the villi, the deeper parts of the intestinal membranes are unaffected by the non-functional FUT2 of non-secretors, due to expression of an alternative 1,2-fucosyltransferase encoded by the H gene 65, 67 . Non-secretors cannot secrete soluble ABO(H) glycans, but might still present suitable docking sites (i.e., Le y ) on these deeper membrane regions, independent of their secretor status, and cooperative binding is expected to be enhanced for hetero-multivalent binding including GM1 55 . Indeed, Cervin et al observed tighter binding of CTB to the crypts than to the villi 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published hetero-multivalent binding model suggests that CTB first binds to a high-affinity ligand such as GM1. Subsequent binding occurs much more readily (up to 10,000-fold faster), also for low-affinity ligands like GM2, since binding is then confined to the 2D membrane surface 54 . In fact, cooperativity was found to be enhanced for a heterogeneous mixture of ligands 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution by Wu and coworkers has been fundamental in this line. In their seminal work, 111,112 Fig . 6 Schematic representation of the rebinding and sliding mechanisms in the interaction of heteromultivalent a-Man/b-Glc bCD-centered heteroglycoclusters with the a-Man-specific lectin ConA as discussed by García Fernández and coworkers.…”
Section: Carbohydrate-lectin Interactions In Heterogeneous Environmenmentioning
confidence: 99%
“…9). 112 The experimental observations cannot be explained on the basis of allosteric regulation, but they are undoubtedly dynamic in nature and associated with the simultaneous presence of the high and low affinity ligands over a certain expression level in a relatively large peripheral area. The fact that going from the bulk to coating is a necessary requisite led the authors hypothesize that the heterocluster effect is mediated by a simple mechanism: reduction of dimensionality (RD).…”
Section: Carbohydrate-lectin Interactions In Heterogeneous Environmenmentioning
confidence: 99%